Garfield gets cookin' - Davis, Jim, 1945 July 28- (New York : Ballantine Books, 2001)
The fat cat serves up a new full-color collection of comic strips, the feline gourmand shares his thoughts on life and food as he devours doughnuts, searches for snacks, and pigs out on pizza, lasagna, and other favorite edible treats
Keywords: Garfield (Fictitious character) -- Comic books, strips, etc